Reproductive activity and vocalizations of Leptodactylus labyrinthicus (Anura: Leptodactylidae) in southeastern Brazil - Zina, Juliana [UNESP]; Haddad, Célio F. B. [UNESP] (Instituto Virtual da Biodiversidade | BIOTA - FAPESP, 2005)
Vocalizations and reproductive activity of two Leptodactylus labyrinthicus populations were studied from Jun/2001 to Feb/2003 in the State of São Paulo, Brazil. Observations began at dusk and ended around 2300 h. Occasionally individuals were monitored throughout the night. Data on reproductive period, calling sites, adult snout-vent length (SVL), oviposition sites, and oviposition period was collected. Leptodactylus labyrinthicus had an extended breeding period associated mainly with rainfall. Males called from the edge of temporary or permanent ponds, began vocalization activity at dusk, and finished around 2300 or 2400h. During the peak of the vocalization period (Dec- Jan), calling activity could extend up to 0400 or 0500h. Three types of vocalizations associated with reproduction were recorded: advertisement call, territorial call, and courtship call. The advertisement call was the most common vocalization. Males and females showed no sexual dimorphism in SVL. However, the males of one population were significantly larger than those of the other population studied. This fact could be explained by frog-hunting in one of the areas, which could wipe out the larger males of the population. Foam nests were recorded mainly in Oct-Nov 2001/2002 in depressions at the edge of temporary ponds, always protected by vegetation. A mean of 6.5% of the eggs present in the foam were fertilized and the other 93.5% possibly are used as a food source by the tadpoles. Mean diameter of the foam nest was 25.4 cm and mean height was 11.4 cm.

Durante os meses de junho de 2001 a fevereiro de 2003 foram estudados os tipos de vocalizações e a atividade reprodutiva de duas populações de Leptodactylus labyrinthicus no Estado de São Paulo. As observações iniciaram-se antes do ocaso e terminaram por volta de 23:00 h. Ocasionalmente, indivíduos foram monitorados durante toda a madrugada. Dados sobre período reprodutivo, sítios de canto, comprimento rostro-cloacal dos adultos (CRC), sítios de desova e período de desova foram coletados. Leptodactylus labyrinthicus apresentou padrão reprodutivo prolongado associado ao período de chuvas na região. Os machos foram encontrados vocalizando às margens de corpos d'água temporários ou permanentes, começaram suas atividades de vocalização ao entardecer e cessaram entre 23:00 e 24:00 h. Durante o pico da estação de vocalização (dezembro a janeiro) a atividade de vocalização cessou por volta de 04:00 e 05:00 h. Foram gravados três tipos de vocalizações com fins reprodutivos: canto de anúncio, canto territorial e canto de corte. O canto de anúncio foi a vocalização mais comumente emitida. Não foi observado dimorfismo sexual quanto ao CRC. No entanto, machos de uma das populações apresentaram CRC significantemente maior do que o de machos da outra população estudada. Provavelmente esta diferença deve-se a atividade de caça à espécie realizada em uma das áreas e os machos maiores poderiam estar sendo exterminados da população. As desovas foram encontradas às margens de corpos d'água temporários, protegidas por vegetação, durante os meses de outubro e novembro de 2001/2002. Nas desovas o número de óvulos fertilizados correspondeu a aproximadamente 6,5% do total de óvulos. Os óvulos não fertilizados possivelmente são usados pelos girinos como fonte de alimento. O diâmetro médio dos ninhos de espuma foi de 25,5 cm e a altura média de 11,4 cm.
Keywords: Anura; Leptodactylus labyrinthicus; reproductive biology; vocalizations; frog-hunting; Anura; Leptodactylus labyrinthicus; biologia reprodutiva; vocalizações; caça